2020
DOI: 10.3389/fphar.2020.586885
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine Alleviates Mouse Colitis and Colitis-Associated Colorectal Cancer

Abstract: Colorectal cancer is one of the most common and lethal cancers in the world. An important causative factor of colorectal cancer is ulcerative colitis. In this study, we investigated the therapeutic effects of piperlongumine (PL) on the dextran sulfate sodium (DSS)-induced acute colitis and azoxymethane (AOM)/DSS-induced colorectal cancer mouse models. Our results showed that PL could inhibit the inflammation of DSS-induced mouse colitis and reduce the number of large neoplasms (diameter >2 mm) of AOM/DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The positive group and the EO dose group could reduce the damage of colon epithelia caused by DSS, also could inhibit inflammatory cell infiltration, and could maintain the integrity of intestinal epithelia and crypt glands. Huang et al found similar results [ 52 ]. The histological score of mice in DSS group was significantly higher than that in normal group ( P < 0.01).…”
Section: Resultssupporting
confidence: 61%
“…The positive group and the EO dose group could reduce the damage of colon epithelia caused by DSS, also could inhibit inflammatory cell infiltration, and could maintain the integrity of intestinal epithelia and crypt glands. Huang et al found similar results [ 52 ]. The histological score of mice in DSS group was significantly higher than that in normal group ( P < 0.01).…”
Section: Resultssupporting
confidence: 61%
“…To improve the prognosis of HBV-HCC patients, we screened 13 small molecule compounds using the CMap database. Piperlongumine can reduce colitis-associated colorectal cancer ( 40 ) and relieve sepsis by attenuating the activation of inflammasomes ( 41 ). From the enrichment results, piperlongumine acts on the HIF-1 signaling pathway and lyase activity, while fisetin regulates NF-kB transcription factor activity.…”
Section: Discussionmentioning
confidence: 99%
“…These doses of PLM were shown to have therapeutic effects against tumor growth in mice without causing obvious adverse effects. 27,28 Meanwhile, mice in the Sham and OVX groups were treated with vehicle solution in the same manner as described above. All injections were given once daily for 6 weeks.…”
Section: Ovariectomy (Ovx)-induced Osteoporosismentioning
confidence: 99%